Role of the state in religious and political motivated conflict in Nigeria / Raji Rafiu Bove - Bove, Raji Rafiu (Faculty of Administrative Science and Policy Studies, 2012)
The central thrust of this paper is to trace the incidences of religious and political induced conflicts in Nigeria and analyze the role played by the state in ameliorating or aggravating the quarrels. The paper espouses the concepts of conflict, politics and religion and tried to locate areas of discord in a multi-cultural cum religious society-Nigeria. It is well known that Nigeria is facing serious religion insurgency which is all consuming; the role played by the state in the ongoing unrest is succinctly examined. The insistence of the government not to negotiate with the insurgent religious groups and thus constituted recalcitrant and intransigent on the part of the state and hence, aggravating the conflict. Also the paper unravels areas where politics has been introduced into the conflict, thus making the conflict intractable. The paper’s conclusion is that for a peaceful resolution of religious and political motivated conflicts the state must be actively engaged through impartial and objective intervention in the crisis and the study shows that pacific rather than force is the quickest means to bring a lasting solution to the political/religious crisis facing the country.